(3eLehY COHjs - (3eLghds ((3eMeO CHhGdhaG s)
(3ChdgG (B:s
(3ef GdehTMGJ GdCfOdSjI, ChdgG ddSGf GdOjf Hf GdNWjH, bhdg(B: (3LGOc GdZjoK EPG GdZjK gei jG ReGf GdhUd HGdCfOdS s
(3BNQgG (B:s
(3dcffj de jcf dj ef jSGYOfj hgG CfG eSYO ef cGf eMRhfG s
(3GddBdiA ef cdGe Ydj Hf CHj WGdH(B, (3h ZjQgs
(3HgG fXGe GdJYbjHIs
(3TYQ h fKQ h jTJed Ydi ehTMGJ CfOdSjI h bUjOI GdefaQLI hdGejI GdYQH ddTfaQj h HGfJ SYGO hQSGdI fKQs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs